Managing expectations : [large type] a memoir in essays - Driver, Minnie (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
A memoir in essays from beloved actor and natural-born storyteller Minnie Driver, chronicling the way life works out even when it doesn't.